Gender matters: factors important for quality of life in midlife after stroke - Matérne, Marie; Jarl, Gustav; Simpson, Grahame; Appelros, Peter; Thermaenius, Ingrid; Lindvall, Mialinn Arvidsson (Frontiers in Neurology, 2025)
BackgroundCoping with disabilities after stroke in midlife can be challenging, with potential gender differences that may have implications for quality of life (QoL) and support. This study aimed to explore QoL and resilience among midlife stroke survivors from a gender perspective.MethodsQuantitative questionnaire data related to demographics, function, service, resilience and QoL were gathered from a stroke register including 51 individuals (of whom 29 were men) aged 40–64 years. Results of gender were compared using two-sided t-tests and chi-square tests. Additionally, eight semi-structured telephone interviews were conducted, with equal representation of men and women. Qualitative content analysis was used to explore deeper and capture nuanced insights.ResultsThe quantitative analysis revealed no statistically significant gender differences. However, the qualitative data revealed three central themes: (1) “A Forced Lifestyle Change,” (2) “Lack of Understanding and Support,” and (3) “Importance of Independence and Coping Strategies.” Men talked about feelings of being restricted in their post-stroke lives and expressed a greater need for support from healthcare providers, family, and friends. In contrast, women described having more well-developed coping strategies and reported a higher perceived QoL.ConclusionQualitative findings suggest men may face greater challenges in adapting to post stroke life. The result suggests that men struggle with accepting limitations that prevent them from participating in social contexts and require more support from healthcare services. These difficulties, potentially due to less effective coping mechanisms, may result in a lower QoL. Gender-sensitive interventions addressing these needs could improve QoL and adaptation.